2015
DOI: 10.1002/2015ja021325
|View full text |Cite
|
Sign up to set email alerts
|

Centrifugal acceleration at high altitudes above the polar cap: A Monte Carlo simulation

Abstract: A Monte Carlo simulation was used to study the outflow of O+ and H+ ions along three flight trajectories above the polar cap up to altitudes of about 15 RE. Barghouthi (2008) developed a model on the basis of altitude and velocity‐dependent wave‐particle interactions and a radial geomagnetic field which includes the effects of ambipolar electric field and gravitational and mirror forces. In the present work we improve this model to include the effect of the centrifugal force, with the use of relevant boundary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…They found that centrifugal forces increase the outflowing O + flux with 2 orders of magnitude when the convection electric field is enhanced from 0 mV/m to 100 mV/m. A similar result has been shown by Abudayyeh et al (2015), who used a Monte Carlo simulation based on the Tsyganenko T96 model and included the effects of the ambipolar electric field as well as gravitational and mirror forces. Additionally, Abudayyeh et al…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…They found that centrifugal forces increase the outflowing O + flux with 2 orders of magnitude when the convection electric field is enhanced from 0 mV/m to 100 mV/m. A similar result has been shown by Abudayyeh et al (2015), who used a Monte Carlo simulation based on the Tsyganenko T96 model and included the effects of the ambipolar electric field as well as gravitational and mirror forces. Additionally, Abudayyeh et al…”
Section: Introductionsupporting
confidence: 77%
“…At an altitude range of 1.2 Re to 15.2 Re, Barghouthi et al (2016) employed the same 1-D Monte Carlo model used by Abudayyeh et al (2015) to investigate energetic H + and O + outflows along two trajectories (from the polar cap to the cusp) and compared them with Cluster data. Considering the centrifugal acceleration, the ambipolar electric field and the waveparticle interaction, they concluded that the latter was the most important mechanism especially at higher altitudes (cusp).…”
Section: Introductionmentioning
confidence: 99%
“…In the latter case the divergence of the geomagnetic field lines converts the perpendicular energy into the parallel direction which increases the parallel velocity. Several acceleration mechanisms were studied such as parallel potential drops [Lundin et al, 1995;Maggiolo et al, 2006], centrifugal acceleration [Cladis, 1986;Horwitz et al, 1994;Demars et al, 1996;Nilsson et al, 2008Nilsson et al, , 2010Abudayyeh et al, 2015a] and wave-particle interaction [Chang and Coppi, 1981;Chang et al, 1986;Retterer et al, 1987Retterer et al, , 1994; Barakat and Barghouthi, 1994;Barghouthi, 1997;Barghouthi et al, 1998;Bouhram et al, 2004;Barghouthi and Atout, 2006;Barghouthi, 2008;Barghouthi et al, 2011;Slapak et al, 2011;Waara et al, 2011Waara et al, , 2012Abudayyeh et al, 2015b].…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 99%
“…where s is a vector along the magnetic field; V E = E × B∕B 2 is the convection velocity; andb is a unit vector in the direction of the magnetic field . For a detailed description of the effect of centrifugal acceleration on the outflow of ions along various flight trajectories above the polar cap refer to Nilsson et al [2008Nilsson et al [ , 2010 and Abudayyeh et al [2015a].…”
Section: 1002/2015ja021990mentioning
confidence: 99%
See 1 more Smart Citation